3D range-modulators for proton therapy: near field simulations with FLUKA and comparison with film measurements. Issue 1 (1st January 2023) - Charuchinda, W; Horst, F; Simeonov, Y; Schuy, C; Penchev, P; Poulsen, P; Sitarz, M; Busold, S; Reidel, C-A; Folkerts, M; Krieger, M; Suwonjandee, N; et al.
Abstract: The 3D range-modulator is a device used in particle delivery systems that can create a highly conformal and homogeneous dose distribution in the target volume with mono-energetic beams, providing an option for high dose-rate FLASH therapy. In the normal case, the modulators are positioned at a typical distance of 30-50 cm in front of the target in order to avoid the fluence ripples resulting from the periodic structure of the modulators. FLUKA Monte Carlo simulation package was used to investigate the fluence distributions of protons penetrating through the 2D range-modulator, the simplified version of the 3D range-modulator, and to determine the minimum distance at which the fluence is homogeneous enough for the treatment. To implement the complex geometry of the modulator in FLUKA, a dedicated FLUKA user routine was developed for the simulation of the periodic pin structures. The highest fluence ripple occurred at a few centimetres behind the modulators and then faded away as the distance increased, which can be described by the edge-scattering effect and later by the blur-out of the overlapping contributions from the pins. Moreover, the dose distribution in water was investigated, particularly for small distances between the modulators and the water phantom. Furthermore, the Monte Carlo results were compared with radiochromic film measurements irradiated with a 3D-printed range modulator and showed a good qualitative agreement. Prospectively, for low modulator-to-target distances, the strong dose inhomogeneities which appear in the proximal part of the target, could introduce additionally a kind of 'mini beam' normal-tissue sparing by the 3D range-modulators.